Proceedings of the 2019 ACM Symposium on Principles of Distributed Computing 2019
DOI: 10.1145/3293611.3331621
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Multiparty Interactive Coding for Insertions, Deletions, and Substitutions

Abstract: In the field of interactive coding, two or more parties wish to carry out a distributed computation over a communication network that may be noisy. The ultimate goal is to develop efficient coding schemes that can tolerate a high level of noise while increasing the communication by only a constant factor (i.e., constant rate).In this work we consider synchronous communication networks over an arbitrary topology, in the powerful adversarial insertion-deletion noise model. Namely, the noisy channel may adversari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…• Silent Rounds. As mentioned in [12], Hoza observed that the ability to have silent rounds can encode information. Essentially, speaking in an odd-numbered round means 1, and speaking in an even-numbered round means 0.…”
Section: Related Workmentioning
confidence: 93%
See 2 more Smart Citations
“…• Silent Rounds. As mentioned in [12], Hoza observed that the ability to have silent rounds can encode information. Essentially, speaking in an odd-numbered round means 1, and speaking in an even-numbered round means 0.…”
Section: Related Workmentioning
confidence: 93%
“…As mentioned in [15], a subsequent work [11] has achieved a better rate of 1 − O( log 1 ) for channels with feedback or erasure channels.Multi-party Case. The multi-party case has also been studied for random [5,25] and adversarial [12,17] corruptions. However, these constructions use large memory and guarantees only O(1) communication overhead for some restricted error rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation